2015
DOI: 10.1530/eje-15-0691
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the intrafamilial correlations and heritability of tumor types in MEN1: a Groupe d'étude des Tumeurs Endocrines study

Abstract: Background: MEN1, which is secondary to the mutation of the MEN1 gene, is a rare autosomal-dominant disease that predisposes mutation carriers to endocrine tumors. Most studies demonstrated the absence of direct genotype-phenotype correlations. The existence of a higher risk of death in the Groupe d'é tude des Tumeurs Endocrines-cohort associated with a mutation in the JunD interacting domain suggests heterogeneity across families in disease expressivity. This study aims to assess the existence of modifying ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
0
25
0
2
Order By: Relevance
“…This association was described for the first time in 1972 by Rosai and coworkers based on three case reports (Rosai et al 1972). TNETs-MEN1 are characterized by genotype-phenotype correlations with MEN1 mutations, strong heritability and a poor outcome with frequent recurrences and a higher risk of death (Goudet et al 2009, Thevenon et al 2015, de Laat et al 2016.…”
Section: Thymic Netsmentioning
confidence: 91%
“…This association was described for the first time in 1972 by Rosai and coworkers based on three case reports (Rosai et al 1972). TNETs-MEN1 are characterized by genotype-phenotype correlations with MEN1 mutations, strong heritability and a poor outcome with frequent recurrences and a higher risk of death (Goudet et al 2009, Thevenon et al 2015, de Laat et al 2016.…”
Section: Thymic Netsmentioning
confidence: 91%
“…The first study reported a twofold higher risk of death in patients bearing a MEN1 mutation affecting menin domain interacting with the transcription factor JunD [13]. The second evidenced a positive intra-familial correlation and trait heritability only for three specific MEN1-associated tumor types: pituitary adenomas, adrenal tumors, and thymic tumors [14]. However, this intrafamilial correlation was shown to decrease progressively when the degree of the genetic relationship was increased, even in presence of the same MEN1 mutation.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, as reported by the great majority of worldwide epidemiology studies, a genotype-phenotype correlation, like in MEN2 syndromes, has not clearly been identified in MEN1 syndrome, strongly reducing the possibility to foresee exact future clinical manifestations of the disease by the specific gene mutation [6,[9][10][11][12]. Recently, two studies by the "Groupe d'étude des tumors endocrines (GTE)" reported a trend for intrafamilial correlation in disease expression and severity and in heritability of MEN1 tumors [13,14]. The first study reported a twofold higher risk of death in patients bearing a MEN1 mutation affecting menin domain interacting with the transcription factor JunD [13].…”
Section: Introductionmentioning
confidence: 99%
“…73 NGS, along with phenotypic criteria and the status of metastasis, has provided clues regarding the molecular/genetic basis of tumors from 797 patients. 74 The diseases of those patients included phenotypic criteria such as the parathyroid and pancreatic NETs as well as the pituitary, adrenal, bronchial, and thymic (thNET) tumors. The somatic Thr372Arg Ying Yang 1 mutation in female patients with sporadic insulinomas (tumor in the beta cells of the pancreas) was identified by whole-exome sequencing.…”
Section: Ngs For Multiple Endocrine Neoplasia Pituitary and Pancreamentioning
confidence: 99%